(untitled) (National Administration Journal, 2025)
Introduction: This article is part of a doctoral research project based on the theoretical postulates of the Competing Values Framework (CVF), updated to measure organizational climate and culture. Objective: The main objective was to identify the predominant archetypes of organizational climate and culture in the nursing and general services departments of a specialized hospital, as well as to identify congruences between organizational objectives and climate and culture. Method: A quantitative approach was used, with descriptive analysis. Results: The findings show a predominance of a control-centered climate and culture, although staff members show a preference for a human relations approach, which is people-oriented. Conclusion: This study reveals a discrepancy between perceived and desired organizational culture in hospital departments, particularly in nursing and general services. While an orientation toward control and stability prevails, staff members prefer a more flexible and people-centered environment. These findings underscore the importance of implementing cultural change strategies that align institutional structures, norms, and values with the expectations of the workforce.